A growing crisis for One Health: Impacts of plastic pollution across layers of biological function - Morrison, Margaret; Trevisan, Rafael; Ranasinghe, Prabha; Merrill, Greg B.; Santos, Jasmine; Hong, Alexander; Edward, William C.; Jayasundara, Nishad; Somarelli, Jason A. (Frontiers in Marine Science, 2022)
The global accumulation of plastic waste has reached crisis levels. Plastic particles ranging from nanometers to meters in size are found throughout every ecosystem on Earth, from the deepest marine trenches to the highest mountains. Plastic waste affects all layers of biological organization, from the molecular and cellular to the organismal, community, and ecosystem-levels. These effects are not only mediated by the physical properties of plastics, but also by the chemical properties of the plastic polymers, the thousands of additives combined with plastics during manufacturing, and the sorbed chemicals and microbes that are transported by the plastic waste. The diverse and multilayered impacts of plastic on biological health prompts an evaluation of these effects from a One Health perspective, through which the complexity of these processes can be integrated and more clearly understood. Using this One Health framework we discuss the following themes: 1) ways in which plastic impacts global health across levels of biological organization, 2) how the effects of plastic interact between layers of biology, and 3) what knowledge gaps exist in understanding the effects of plastic within and between biological scales. We also propose potential solutions to address this growing crisis, with an emphasis on One Health perspectives that consider the oneness of animals, humans, and the environment.